On a critical Kirchhoff-type problem. (March 2020) - Faraci, Francesca; Farkas, Csaba
Abstract: In the present paper we study a Kirchhoff type problem involving the critical Sobolev exponent. We give sufficient conditions for the sequentially weakly lower semicontinuity and the Palais–Smale property of the energy functional associated to the problem.